Evaluasi Usability dan Perbaikan Antarmuka pada Laman Utama kominfo.go.id - Santika Sari; Amelia Rizky Ramadhan (Universitas Indraprasta PGRI Jakarta, 2021)
As the vanguard of information delivery, the Ministry of Communication and Information Technology of the Republic of Indonesia has a main Web Page with a prominent role. However, it turns out that there are still many people who complain about the difficulty in operating some features on the Ministry of Communication and Information Technology's Web Page (kominfo.go.id) and about the mismatches between the features and psychological and ergonomic factors. These are the usability problems found on the kominfo.go.id page. Some parameters that can be used as benchmarks in measuring web usability criteria are comprised of Learnability, Efficiency, Memorability, Errors, and Satisfaction. The settlement method that will be used is the usability testing to be carried out by observing the users, the data of which are taken and then analyzed to produce the results to be used as a reference for improvement suggestions. Improvement suggestions are realized by redesigning the interface of the kominfo.go.id web page using several methods in designing the web page interface, one of which is a Human-Centered Design method. The usability level of the kominfo.go.id web page is quite far from the tolerance limit. It should be at least 75% efficiency level, but kominfo.go.id only gets 18% efficiency level. Therefore, it is necessary to hold the improvement of the user interface